(untitled) (Eurasian Journal of Engineering and Technology, 2025)
The article presents the results of experiments conducted on a rotary filter apparatus, in which the modes of gas and liquid mixtures were studied. As a result of experimental tests, the friction coefficients between the contact elements of the basalt thrust and the hydraulic thrust were determined. As a result of these studies, it was found that a certain amount of ionizing radiation energy is required for optimal separation of gases and gas mixtures in liquids and gaseous media.